DINAMIKA DAN TANTANGAN PENERAPAN PENGAWASAN KLINIS DALAM MENINGKATKAN PROFESIONALISME GURU - Nur Widyasari; Muhammad Husain; Aden Paryoga; Zulaikha Fitria; Mustofa Kemal (Universitas Islam Negeri (UIN) Sumatera Utara, 2024)
This study aims to identify the challenges and dynamics in the implementation of clinical supervision to improve the professionalism of educators at MA Mukhtar Syafa'at school. The method used is a descriptive qualitative approach with data collection through in-depth interviews, direct observation, and documentation analysis. Key informants include educational supervisors, principals, and teachers. The results of the study indicate several major challenges in the implementation of clinical supervision, including differences in perception between supervisors and teachers regarding the purpose of supervision, lack of skills of supervisors in providing constructive feedback, and high teacher workloads that limit participation in supervision. In addition, it was found that clinical supervision is often considered an administrative formality without providing a significant impact on teacher professional development. Observations also revealed that although the reflective approach has begun to be implemented, its implementation is often inconsistent. This study recommends the need for ongoing training for supervisors to improve supervision competencies, integration of clinical supervision with teacher work schedules, and development of supervision guidelines that are relevant to the local context. These findings are expected to provide strategic insights to improve the effectiveness of clinical supervision and support educator professionalism in a sustainable manner